Reimagining Islamic Family Law through Climate Change: The Role of Sharia in Sustainable Household Ethics - Liza, Fitri; Luhuringbudi, Teguh; Ali, AM Hasan; Alrumayh, Safa Husayn; Luhur, Mujhid Budi (Tuah Foundation, 2026)
This article reconstructs Islamic family law in response to the household-level consequences of global climate change, placing ecological resilience within the framework of maqāṣid al-sharīʿah (the higher objectives of Islamic law). It argues that the stability of the Muslim household (ṣulb al-usrah al-islāmiyyah) cannot be separated from the twin duties of istiʿmār al-arḍ (stewardship of the earth) and ḥifẓ al-bīʾah (protection of the environment). To develop that argument, the article draws together three analytical traditions: Jasser Auda’s maqāṣid al-sharīʿah Systems Theory, David Schlosberg’s Ecological Justice Theory, and Margaret Urban Walker’s Everyday Ethics Theory. The research is qualitative and descriptive, applying critical hermeneutics to classical works in uṣūl al-fiqh and fiqh al-usrah alongside contemporary scholarship on Islamic environmental ethics. The findings indicate that climate resilience within Islamic family law depends less on technological or economic adjustment than on the ethical resources already embedded in the sharīʿah value system. The novelty of the study lies in its repositioning of Islamic family law as a framework of micro-ethical governance, one that operationalizes ecological justice at the level of the home and connects classical juristic reasoning with the climate debates of the present.